2017
DOI: 10.1039/c7cp05249a
|View full text |Cite
|
Sign up to set email alerts
|

Solvation of apolar compounds in protic ionic liquids: the non-synergistic effect of electrostatic interactions and hydrogen bonds

Abstract: The solvation properties of protic ionic liquids such as alkylammonium salts are still virtually uncharacterized. Both electrostatic interactions between charged particles and hydrogen bond networks in a solvent are known to hinder the solubility of apolar species. Protic ionic liquids can be a priori expected to dissolve hydrocarbons worse than aprotic ionic liquids which do not form hydrogen bonds between the ions. We measured the limiting activity coefficients of several alkanes and alkylbenzenes in propyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…However, here we do observe a tendency of higher CH 4 solubility in comparison with similar aprotic ionic liquids. Sedov et al [ 17 ] explain this behaviour by a preferential cavity formation and favorable solvation of hydrocarbons in the apolar domain of nanostructured protic ionic liquids. Consequently, the higher CH 4 permeability values measured for SILM S prepared from protic ionic liquids would be expected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, here we do observe a tendency of higher CH 4 solubility in comparison with similar aprotic ionic liquids. Sedov et al [ 17 ] explain this behaviour by a preferential cavity formation and favorable solvation of hydrocarbons in the apolar domain of nanostructured protic ionic liquids. Consequently, the higher CH 4 permeability values measured for SILM S prepared from protic ionic liquids would be expected.…”
Section: Resultsmentioning
confidence: 99%
“…The solubilities of CO 2 , CH 4 , C 2 H 6 , N 2 and O 2 in several aprotic ILs have been studied extensively [ 12 , 13 , 14 , 15 ]. On the contrary, the thermodynamic properties of protic ionic liquids, i.e., those comprising proton-donor and proton-acceptor centers in their molecules, have been investigated in lower extent [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been performed to understand its fundamental properties. [5][6][7][8] Ludwig et. al.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the PILs exhibit more interesting properties due to H‐bonding abilities of cations or anions and hence may have more potential applications in drug formulations . Physicochemical studies of PILs and other ionic liquids such as amino acid ionic liquids indicated that the cooperative H‐bonding is the main factor responsible for their observed high hydration numbers than those expected from the H‐bond donor acceptor sites available …”
Section: Introductionmentioning
confidence: 99%